The Effect Of The Work Environment On Employee Performance At The Binjai City Social Service - Hendra Fereddy Sitorus; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of the work environment on employee performance at the Binjai City Social Service. A good work environment is expected to increase employee comfort, motivation, and productivity, which ultimately contributes to organizational performance. The method used in this study is a quantitative approach with a correlational descriptive design. The data was obtained through a questionnaire distributed to 50 employees at the Binjai City Social Service. Data analysis was carried out using simple linear regression with the help of the SPSS program. The results of the study show that the work environment has a positive and significant effect on employee performance. The regression coefficient of 1.475 shows that every one-point increase in the work environment variable will increase employee performance by 1.475 points. In addition, the Adjusted R Square value of 0.555 shows that 55.50% of the variation in employee performance can be explained by the work environment, while the rest is influenced by other factors that are not studied. The t-test produced a t-count value of 8.133 which was greater than the t-table (2.00575) with a significance level of 0.000 (p < 0.05), which showed a significant relationship between the two variables. Based on the results of the research, it is recommended for the Binjai City Social Service to improve a conducive working atmosphere, improve interpersonal relationships between employees, and provide more adequate work facilities. Further research is also recommended to explore other factors that can affect employee performance, such as motivation and leadership.